Heart Failure Caused by Incidentally Discovered Right Atrial Myxoma: A Rare Case Report - Atikah, Rahmatulhusna; Meilus, Budi Patria (CV. Publikasi Indonesia, 2025)
Primary cardiac tumors, though uncommon, play a significant role in medical practice. Cardiac myxoma is the most common benign cardiac tumor, characterized by varying symptoms depending on the location and size of the tumor. We report the case of a 44-year-old woman with complaints of shortness of breath, upper abdominal pain, and leg oedema. Right atrial myxoma was incidentally found after an echocardiography examination, which is an essential tool for detecting and diagnosing cardiac tumors. The patient exhibited clinical improvement with inotropic therapy and antibiotics and was referred for surgical removal of the tumor. Cardiac myxoma surgical procedures generally have a favorable prognosis with a high survival rate. However, postoperative complications such as arrhythmias and infections require close monitoring. Thus, early diagnosis and appropriate management are essential in addressing cardiac myxoma.